Analysis of the production efficiency of peanut crop in Al-Ghab area (Journal of Hama University, 2025)
This research aimed to analyze the productive efficiency of peanut crop in Al-Ghab area for the agricultural season 2024. It relied on a traditional questionnaire form in which the primary data were collected through personal interviews with a random sample of (150) farmers. The primary data were analyzed using the descriptive and quantitative analysis method by calculating some different measurements represented in estimating regression and correlation models, estimating the production function, and measuring production elasticities in addition to using the data envelope method (DEA), which relies on the linear programming method to obtain the optimal solution, in order to measure the productive efficiency of peanut crop.        The results of the study showed that the costs of land rent, irrigation water and seeds constituted the largest proportion (48.5%) of the total costs of producing a hectare of peanuts in the studied area, and the economic return rate for producing 1 hectare of peanuts was 60.8%, which indicates that the efficiency and profitability of the invested money was approximately 61%, which is considered a good percentage, and the net profit margin rate was 37.8%, which indicates achieving a net profit of 38% of the revenues and 62% goes to production costs.        It was also found that there was a positive and statistically significant relationship between the amount of peanut production per hectare used in seeds and the amount of phosphate fertilizer, as well as nitrogen fertilizer and soluble potassium fertilizer. The average value of production efficiency, given the constant return to capacity, reached 83% for the total sample. It was found that production efficiency increased with the increase in area, as the fourth holding category (greater than or equal to 2 ha) was the best category, as the production efficiency rate reached about 89%.